How do virtual and relational ties affect international opportunity realization for emerging market born-global firms? A contingency model - Jean, Ruey-Jer “Bryan”; Kim, Daekwan; Cavusgil, Erin; Tsuteaki, Hayashi; Ojala, Arto (Elsevier, 2025)
How do entrepreneurs use virtual relationships to identify and capitalize on international opportunities? While it is widely recognized that, in the age of virtual interconnectedness, businesses thrive on relationships that they establish over the Internet, its role and significance remain to be fully understood. Drawing on entrepreneurship, social networks, and information processing theory, we propose a contingent model of virtual and relational ties on international opportunity realization. Empirical findings from a survey of 273 Chinese Born Global firms indicate that both virtual and relational ties have positive effects on international market opportunity realization and the effect is not significantly different. In addition, the value of virtual and relational ties is dependent on task and environmental uncertainty. Virtual ties are more valuable when foreign markets are diverse and domestic institutions are uncertain. Relational ties are more effective in the pursuit of international opportunity when products are complex. However, relational ties are less effective when: technology is changing rapidly, foreign markets are diverse, and domestic institutions are uncertain.
Keywords: Virtual ties; Relational ties; International opportunity; Born global firms; emerging markets; fi=Kansainvälinen liiketoiminta|en=International Business|